VALIDASI METODE ANALISIS DAN PENGUJIAN FORCE DEGRADATION STUDY PADA MEREK DAGANG YANG MENGANDUNG PARACETAMOL - Chresiani Destianita Yoedistira; Gytha Novella Ongkowijoyo (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
Paracetamol is the drug most consumed by the public,so it’s necessary to carry out strict quality assurance. Therefore, a forced degradation study was carried out using a UV-Vis spectrophotometer with various degradation conditions recommended by ICH. The research was conducted on five brands of paracetamol tablets that were treated with hydrolysis, oxidation, photolytic, and thermal treatment, which were detected by UV-Vis spectrophotometer at a wavelength of 243nm. The developed method is validated with linearity, selectivity, accuracy, precision, detection limit, and quantification parameters. The results obtained are selective, linear with a regression of 0.99; accurate with %Recovery between 99.4 - 100.9% and %CV <2%; and precision with %RSD <2%; LOD 24.35706967 mg/L; LOQ 79.95750448 mg/L. The five brands of drugs tested were subjected to hydrolysis, oxidation, photolysis, and thermal degradation. Under alkaline and oxidizing conditions, it was found that the degradation was beyond the limit of levels, according to the Indonesian Pharmacopoeia 90% - 110%.